Between disgust and indifference: Affective and emotional relations with carp (Cyprinus carpio) in Australia. Issue 4 (18th June 2019) - Atchison, Jennifer
Abstract : As the product of not always rational human thought, emotions are either excluded from or considered to be barriers to effective invasive species management. In a context where fish are still disregarded, in this paper I consider the affective and emotional geographies of the world's most broadly distributed freshwater fish, carp ( Cyprinus carpio ) in Australia, in emerging sites of management that involve killing. Invasive species management is yet to reconcile emotion and the affective politics of killing invasive animals as a normative and ongoing practice of care for the environment. This paper advances animal geographies by developing a conceptual understanding of the biopolitics of invasive life and invasive species management by thinking through carp as affective and emotional subjects. To do this I look to feminist approaches that conceptualise emotion as relational, including Ahmed's analysis of emotion as movement, and visceral geographies' extension of embodied meaning‐making beyond the human. Drawing on original empirical analysis of managing carp, I identify how carp are performed as collectively disgusting or monstrous objects and how emotions are submerged and people can become indifferent to, or "pull away" from, ethical deliberation. However, attending to affect and emotion beyond the human subject also allows carp to emerge as different kinds of "spooky" subjects who, through conflicting, constantly changing, and more‐than‐invasive relationships, resist singular and hegemonic understandings. Taking a feminist approach allows me to consider how carp have affective biopolitical agency, in life and death, across these multiple subjectivities with power to transform human relationships with nature by situating and re‐engaging people in the problems of the world. Indeed, I argue that it is through the affective and emotional practices of managing carp that people might also begin to apprehend their responsibilities and limitations in the Anthropocene. Abstract : As invasive fish, carp are excluded from efficacy and ethical concerns regarding their management. Looking to feminist and relational approaches, this paper considers embodied and emotional responses to carp in emerging sites of management that involve killing. Although emotion is often thought of as a barrier or obstacle to efficient and effective management, I argue emotion provides both transformative and situated opportunities for thinking about future relationships with invasive species and with the environment more broadly.